Perkawinan Anak Di Bawah Umur dalam Perspektif Hukum Islam dan Sosiologi Hukum - Fathoni, Alvan (JURNAL AT-TURAS, 2017)
This article portrays the marriage of underage children in terms of Islamic law, state act, and sociology of law. This study argues that such marriage is an unfinished social issue although state or Islamic law ruled the minimum limit for possibility of marriage. However, many rural people have culturally been constructed within different situation from the urbans, so it created more chances for them to get marriage under the possible age. The underage marriage still happens since the society had sociologically believed that a child who had marriageable age (balîgh) must be married, since it causes the more possible disadventages (madhârat), such as doing the religiously forbidden things.